Mr. Stink - Walliams, David, 1971-; Blake, Quentin (London : Harper Collins, 2009)
Twelve-year-old Chloe, who does not feel like she fits in at school or with her family, is happy to befriend a local tramp she calls Mr. Stink, but when her mother decides to run for local office and rid the town of homeless people, Chloe must figure out a way not to lose her only friend.
5.6
5-8
Keywords: Friendship -- Juvenile fiction; Sisters -- Juvenile fiction; Tramps -- Juvenile fiction; Friendship -- Fiction; Sisters -- Fiction; Tramps -- Fiction; Friendship -- Fiction; Sisters -- Fiction; Tramps -- Fiction